Learning Analytics as a tool in academic learning contexts: Possible impacts on social inclusion - Zona, Umberto; De Castro, Martina (Education Sciences & Society - Open Access, 2019)
In the field of teaching and learning processes, the potential of Learning Analytics is one of the topics that is attracting most interest in the scientific community. However, it would be important to place L.A. within a historical perspective, able to focus on the scientific, cultural and social roots of this approach. This would also allow us to address a question that cannot be overlooked, namely whether Learning Analytics is one of the teaching technologies or, rather, should be understood as a new global approach to learning processes. In our opinion, L.A. are placed at the crossroads between the formal and informal dimensions of learning and are part of the behaviorist tradition, with the aim of identifying the behavioural clusters that recur most frequently and which are considered to adhere to predefined performance standards. The search for the performative standard typical of L.A., not considering the differences, the peculiarities and the specific personal abilities as of the resources, seems, moreover, to refer to the system/model of the integration that, in a homologating perspective more than inclusive, sets objectives on the basis of a presumed normality, ignoring Specific Learning Disorder (SLD) and Special Educational Needs and Disability (SEND).